Hubungan antara Fear of Missing Out (FOMO) dengan Keputusan Pembelian pada Generasi Z sebagai Konsumen Produk Fast Beauty - Rahel Sibuea; Agoes Dariyo (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
The Fast Beauty phenomenon presents social pressure from marketing strategies that create a feeling of worry about being left behind, thus encouraging generation Z consumers to purchase beauty products in the Fast Beauty brand category. This study aims to examine the relationship between Fear of Missing Out (FoMO) and purchase decisions among generation Z as consumers of Fast Beauty products. The method used in this study was a quantitative correlational method with 200 participants aged 18 to 30 years, of which 7 male (3.5%) and 193 female (96.5%). Data collection was conducted through an online questionnaire compiled using the Missing Out Scale (FoMOS) and a Purchase Decision scale using a Likert scale of 1 to 4. The analysis results show a significant positive relationship between Fear of Missing Out (FoMO) and purchase decisions (r = 0.620, p < 0.05), where the higher the Fear of Missing Out (FoMO), the higher the tendency of Generation Z consumers to make Fast Beauty product purchases. These analysis results align with previous research showing that consumers experiencing Fear of Missing Out (FoMO) tend to make product purchases without careful consideration due to concerns about being left behind in their social environment. The implications of this research show the importance of implementing marketing strategies that pay more attention to the psychological side of consumers and the implementation of more conscious consumer behavior before purchasing Fast Beauty products.